2020
DOI: 10.1111/1471-0528.16361
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of routine first trimester combined screening for pre‐eclampsia: a clinical effectiveness study

Abstract: Objective Evaluate clinical effectiveness of the first trimester combined (FMF) pre-eclampsia screening programme when implemented in a public healthcare setting. Design Retrospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
128
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(138 citation statements)
references
References 18 publications
5
128
0
3
Order By: Relevance
“…Since HDsP continue to be a leading cause of maternal and Perinatal mortality and morbidity with direct estimated maternal deaths of about 41000 per year (14% of all maternal deaths), of whom 94% occurred in low-income countries [27] attempts continue to find modes of prediction and prevention. Peguero et al [28] Guy et al [30] have reported that first trimester combined screening for pre-eclampsia, maternal risk factors, blood pressure, PAPP-A and uterine artery Doppler indices, is both feasible and effective in public healthcare settings. Various attempts continue for prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Since HDsP continue to be a leading cause of maternal and Perinatal mortality and morbidity with direct estimated maternal deaths of about 41000 per year (14% of all maternal deaths), of whom 94% occurred in low-income countries [27] attempts continue to find modes of prediction and prevention. Peguero et al [28] Guy et al [30] have reported that first trimester combined screening for pre-eclampsia, maternal risk factors, blood pressure, PAPP-A and uterine artery Doppler indices, is both feasible and effective in public healthcare settings. Various attempts continue for prevention.…”
Section: Discussionmentioning
confidence: 99%
“…5 We believe that the scientific data now overwhelmingly support the need to re-evaluate current service provision for pre- Re: Implementation of routine first trimester combined screening for pre-eclampsia: a clinical effectiveness study Sir, We congratulate Dr Guy et al on their paper, which demonstrates that the implementation of combined screening using the Fetal Medicine Foundation (FMF) algorithm is feasible in practice, and is better than the existing National Institute for Health and Care Excellence (NICE) guidelines in the prevention of pre-eclampsia, especially preterm preeclampsia with delivery before 34 weeks of gestation. 1,2 We hope that this will lead to the wider application of combined screening for the prediction and prevention of pre-eclampsia.…”
Section: Sirmentioning
confidence: 99%
“…We would like to thank Professors Wright and Nicolaides for their comments 1 on our clinical effectiveness study 2 and share their hopes for the wider implementation of a combined screening programme for pre‐eclampsia prevention in our public health systems. We agree with their emphasis on the importance of accounting for the effect of aspirin when assessing predictive performance of the combined screening test for pre‐eclampsia – hence our formal acknowledgment of this issue in our paper.…”
mentioning
confidence: 99%
“…We congratulate Dr Guy et al. on their paper, which demonstrates that the implementation of combined screening using the Fetal Medicine Foundation (FMF) algorithm is feasible in practice, and is better than the existing National Institute for Health and Care Excellence (NICE) guidelines in the prevention of pre‐eclampsia, especially preterm pre‐eclampsia with delivery before 34 weeks of gestation 1 , 2 . We hope that this will lead to the wider application of combined screening for the prediction and prevention of pre‐eclampsia.…”
mentioning
confidence: 99%